Second wave of COVID-19: more hype than reality - Rajiva, Rajiva; Mahalingam, Muruganantham; Basavaraj, Thumabalabeedu; Pardal, Maninder Pal Singh; Saxena, Aaditya; Chary, Sridhar; Mahar, Sandeep Singh (International Journal Of Community Medicine And Public Health, 2022)
Background: The second wave of COVID-19 hit India with the nation reporting over 4 lakh cases daily since second week of April 2021. Keeping in view the lack of adequate data in this regard; and the public health importance of the second wave of the Covid-19 pandemic, the researchers proceeded to carry out the study. The aim of the study was to study the clinicoepidemiolgical profile of hospitalised COVID19 cases in an urban area. Methods: The workers carried out a cross sectional descriptive study. Period of the study was April 2021 to September 2021. Detailed epidemiological, clinical, laboratory and radiological data was obtained in respect of 149 cases of Covid-19. Results: Mean age of the cases was 39.79 years. One hundred and twelve (75.17%) cases were males, while thirty- seven (24.83%) were females. One hundred and twenty-nine (86.57%) gave history of fever. Eight (6.04%) cases were totally asymptomatic. Clinical condition of six (4.02%) cases necessitated them to be placed on ventilator for various periods of time. Eight (5.36%) cases were administered oxygen for various periods of time. All the cases recovered after varying periods of time; and there were no fatalities. Diabetes mellitus was the commonest comorbidity; and it was seen in twenty (13.42%) of cases. Conclusions: Our study has indicated that symptomatology of the disease may vary over time. The researchers believe that the most important conclusion of our work is that the world must remain alert to the characteristics of the virus and the disease.